2005
DOI: 10.1590/s0102-09352005000600002
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of reproductive failure in dairy herds from Goiânia

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It is much higher than findings of Feyissa (2000) and Mekibib et al (2013), where it was 5.1 and 2.32% only. Similarly, Andrade et al (2005) found cervical inflammation in 0.6% cases only. This variation could possibly be due to reason that only abandoned infertile cows were studied.…”
mentioning
confidence: 85%
“…It is much higher than findings of Feyissa (2000) and Mekibib et al (2013), where it was 5.1 and 2.32% only. Similarly, Andrade et al (2005) found cervical inflammation in 0.6% cases only. This variation could possibly be due to reason that only abandoned infertile cows were studied.…”
mentioning
confidence: 85%
“…These findings corroborate those presented in this study, which demonstrate that Staphylococcus aureus was the main agent isolated (41.65%), followed by enterobacteria (37.50%). Andrade et al (2005) studied 2823 breeding females of the Holstein and Gir breeds in Brazil and reported that the main pathogens found in the herd were Gram-positive cocci (41.3%) and Gram-negative rods (52.6%), with Staphylococcus aureus and Escherichia coli being the main pathogens found in uterine infections. In vitro tests demonstrated that these microorganisms showed a higher susceptibility to chloramphenicol, gentamicin, and neomycin.…”
Section: California Mastitis Test (Cmt) and Microorganisms Associatedmentioning
confidence: 99%
“…The susceptibility of bacteria was 100% to sulfazotrim, 77.7% to chloramphenicol, and 66.6% to vancomycin, the other antibiotics did not have significant results (Table 3). According to Andrade et al (2005), the percentage of microorganisms' resistant to different drugs is a complicating factor for prophylactic and therapeutic regimens for the control of ISSN 2166-0379 2020 uterine infections and consequently intra-mammary infections. This resistance is probably associated with the indiscriminate and incorrect use of antibiotics, often without determination of the susceptibility of the microorganisms to the drugs (Andrade et al, 2005), with the acquisition of antimicrobial resistance, and with the biofilm-forming ability of the bacteria (Taponen and Pyörä lä , 2009).…”
Section: Susceptibility Of Microorganisms Associated With Mastitismentioning
confidence: 99%